Modified titanium magnesium phosphate material, preparation and application thereof
Patent Information
- Application Number
- CN202410499537.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-04-24
AI Technical Summary
The existing titanium magnesium phosphate materials have low purity, resulting in low electrical conductivity. Furthermore, they are prone to sticking to the crucible and generating impurity phases during the preparation process, which affects their electrochemical performance.
Modified titanium magnesium phosphate material was prepared by replacing Ti4+ in titanium magnesium phosphate with Al3+/Cr3+, using titanium pyrophosphate as the phosphorus and titanium source, and sintering in one step. The doping amount was controlled within the range of 0.01≤x≤0.06. Combined with sand milling and spray drying processes, the formation of saggars and impurity phases was avoided.
The modified titanium magnesium phosphate material has improved purity and ionic conductivity, simplified the preparation process, is suitable for large-scale production, and enhances the performance of solid-state batteries.
Smart Images

Figure CN118561251B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a modified titanium magnesium phosphate material and its preparation and application. Background Technology
[0002] Lithium-ion batteries are considered the most promising energy storage and power source. Currently, they are widely used in portable rechargeable devices and high-power electric vehicles. However, due to the limited lithium reserves on Earth, the development of next-generation metal-ion batteries is urgently needed to meet current human needs.
[0003] High-safety solid-state lithium-ion batteries are currently a hot research topic, and solid-state electrolytes are key to the research of all-solid-state batteries. Titanium magnesium phosphate, as a NASICON-type solid electrolyte, can stably store alkali metal and alkaline earth metal ions, such as Li ions, Na ions, and Mg ions, and has good development potential.
[0004] The most common method for preparing titanium magnesium phosphate is solid-state sintering, a relatively simple process suitable for large-scale industrial production. However, during the raw material mixing and sintering process, the resulting titanium magnesium phosphate powder tends to stick to the crucible, affecting production efficiency and introducing impurities during powder transfer. Furthermore, in solid-state reactions, commonly used phosphorus-containing substances are easily affected by moisture, leading to raw material adhesion and uneven distribution of Mg in the precursor, resulting in Mg enrichment and ultimately the formation of titanium pyrophosphate impurities. The presence of impurity phases reduces its ionic conductivity and affects its electrochemical performance, limiting the application of current titanium magnesium phosphate materials. Summary of the Invention
[0005] The present invention aims to overcome the defect of low electrical conductivity caused by low purity of titanium magnesium phosphate materials in the prior art, and provides a modified titanium magnesium phosphate material and its preparation and application to overcome the above defects.
[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a modified titanium magnesium phosphate material, wherein the modified titanium magnesium phosphate material is made by using M-containing... 3+ It is obtained by one-step sintering of M source, magnesium source, titanium pyrophosphate and titanium dioxide; the general formula is Mg 0.5+x Ti 2-x M x (PO4)3, M is Al or Cr, 0.01≤x<0.06.
[0007] The inventors of this application introduced Al into magnesium titanium phosphate. 3+ / Cr 3+Modifying titanium magnesium phosphate makes it less prone to the formation of impurity phases, improving its purity and further enhancing its ionic conductivity. This is mainly due to the Ti content of titanium magnesium phosphate. 4+ By Al 3+ / Cr 3+ Substitution will introduce more Mg 2+ To maintain electrical neutrality, and to supplement Mg 2+ The impurity phase can be further transformed into magnesium titanium phosphate conductive crystals. And Al... 3+ / Cr 3+ Cationic-substituted titanium magnesium phosphate Ti 4+ Can broaden Mg 2+ The migration channels increase the number of charge carriers and improve ionic conductivity.
[0008] It is important to note that the dopant content should be controlled within a certain range; neither too much nor too little doping is advisable. This is because excessive doping with exogenous ions can lead to lattice distortion, thereby interfering with the NASICON-type structure suitable for carrier migration and causing capacity decay. Insufficient substitution will result in unsatisfactory electrochemical performance and may also lead to the formation of impurity phases. Therefore, the dopant content should be controlled within a specific range.
[0009] Furthermore, the selection of trivalent cations is based on their affinity for Ti. 4+ With closer ionic radii and smaller valence state differences, it is easier for substitution to occur and less likely to cause strong lattice distortion and twisting under trace doping. It can maintain the original crystal phase of titanium magnesium phosphate to the maximum extent and retain the excellent electrochemical performance of titanium magnesium phosphate. Furthermore, it can enhance the performance of titanium magnesium phosphate by modifying it based on its original excellent electrochemical performance.
[0010] Electrochemical performance test results show that the ionic conductivity of the doped magnesium titanium phosphate, compared with that of the unmodified magnesium titanium titanium phosphate, is 1.39 × 10⁻⁶. -4 S / cm increased to 4.01×10 -4 S / cm. XRD results can help prove that the spectrum of the modified titanium magnesium phosphate material is closer to the standard card, with no extraneous impurities. This proves that the modified material is produced by Al 3+ / Cr 3+ Modified and doped titanium magnesium phosphate materials have higher purity and higher ionic conductivity, which can broaden their application scope.
[0011] More preferably, the modified titanium magnesium phosphate material has the general formula Mg 0.5+x Ti 2-x M x (PO4)3, 0.01≤x≤0.05.
[0012] This invention also provides a method for preparing modified titanium magnesium phosphate material, comprising the following steps: S1, containing M 3+ M source, magnesium source, titanium pyrophosphate, and titanium dioxide are uniformly dispersed in water / alcohol reagent to obtain a mixed slurry; S2. The mixed slurry obtained in S1 is milled, dried, and then sintered to obtain a product with the general formula Mg. 0.5+x Ti 2-x M x Modified titanium magnesium phosphate material of (PO4)3 (0.01≤x<0.06); where M is Al or Cr.
[0013] Because titanium and phosphorus readily combine, titanium pyrophosphate impurities often appear during the general preparation of titanium magnesium phosphate due to incomplete sintering. While the content of titanium pyrophosphate in titanium magnesium phosphate is low, it is extremely difficult to remove, requiring repeated crushing and sintering, resulting in significant costs.
[0014] The inventors of this application selected titanium pyrophosphate as both the phosphorus and titanium source, reducing the chance of titanium and phosphorus bonding and preventing the generation of large amounts of titanium pyrophosphate impurities during the sintering process of titanium magnesium phosphate. Furthermore, through Al... 3+ / Cr 3+ The introduction of this process transforms the impurity phase into conductive titanium magnesium phosphate crystals, thus ensuring the purity of the modified titanium magnesium phosphate.
[0015] It is worth noting that titanium pyrophosphate is used here as the phosphorus source, replacing the commonly used phosphorus pentoxide. This avoids the problems caused by the moisture absorption of phosphorus pentoxide, which leads to material sticking, uneven mixing, and sticking to the crucible. While avoiding sticking to the crucible and making it difficult to recycle the crucible used in subsequent sintering, it also ensures that the phosphorus source is fully mixed with other raw materials, promoting the formation of titanium magnesium phosphate.
[0016] Preferably, in step S1, the magnesium source is selected from one or more of magnesium carbonate, magnesium oxide, magnesium hydroxide, and magnesium phosphate.
[0017] More preferably, the magnesium source is in excess.
[0018] In the process of modifying titanium magnesium phosphate, Ti 4+ By Al 3+ Substitution will introduce more Mg 2+ To maintain electrical neutrality, and to supplement Mg 2+ The impurity phase can be further transformed into magnesium titanium phosphate conductive crystals. Maintaining an excess magnesium source is beneficial for providing more Mg. 2 + This helps transform the impurity phase during the formation of titanium magnesium phosphate, ultimately yielding high-purity titanium magnesium phosphate material.
[0019] Preferably, in step S1, the alcohol reagent is selected from any one of ethanol, propylene glycol, and polyvinyl alcohol.
[0020] Preferably, in step S1, the solid content of the mixed slurry is 15~35 wt%.
[0021] More preferably, the solid content of the mixed slurry is 15-30 wt%.
[0022] More preferably, the solid content of the mixed slurry is 20-30 wt%.
[0023] Preferably, in step S2, the average output particle size of the sand mill is less than 0.3 μm, and the rotation speed is 1500-2000 rpm.
[0024] Sand milling can increase the uniformity of the mixture and greatly reduce the average particle size of the raw materials, allowing for more thorough contact between the raw materials, maximizing the bonding between the titanium and magnesium sources, and increasing the reactivity of the raw materials during solid-state sintering.
[0025] More preferably, the rotational speed is 1800 rpm.
[0026] Preferably, in step S2, the drying method is selected from any one of the following: oven drying, vacuum rake drying, and spray drying.
[0027] Preferably, the spray dryer has an outlet temperature of 110~140℃, an inlet temperature of 280~300℃, and a pressure of 0.4~0.5MPa.
[0028] More preferably, the spray dryer is a pneumatic spray dryer.
[0029] Pneumatic spray dryers produce loose powder after processing, avoiding the need for subsequent crushing and ball milling operations required by other drying methods. This simplifies the processing flow, improves production efficiency, and facilitates large-scale production.
[0030] Preferably, in step S3, the sintering temperature is 900~1100℃, the sintering time is 6~12 h, and the heating rate is 2~5℃ / min.
[0031] The present invention also provides the application of the above-described modified titanium magnesium phosphate material or the modified titanium magnesium phosphate material prepared by the above method in solid-state batteries.
[0032] Solid-state batteries made from the modified titanium magnesium phosphate material exhibit significantly improved ionic conductivity. In practical applications, batteries made from high-ionic-conductivity electrolyte materials possess higher energy density, faster charging speeds, and longer cycle life. Therefore, the modified titanium magnesium phosphate material proposed in this invention has significant practical value.
[0033] Therefore, the present invention has the following beneficial effects: (1) The Al used in this invention 3+ / Cr 3+ Ti in magnesium titanium phosphate 4+ Ions, introducing excess Mg 2+ By balancing the charge, the added Mg can further transform the generated impurity phase into the conductive crystalline phase of magnesium titanium phosphate, thereby improving the purity of magnesium titanium phosphate.
[0034] (2) The preparation method provided by the present invention uses titanium pyrophosphate as both the phosphorus source and titanium source in the preparation of titanium magnesium phosphate, which avoids the sticking of commonly used phosphorus sources such as phosphorus pentoxide due to moisture and uneven mixing, and solves the problem of easy sticking of titanium magnesium phosphate to the sintering crucible in the prior art.
[0035] (3) The modified titanium magnesium phosphate material prepared by the present invention can be used as an ideal solid electrolyte material in solid batteries. Its preparation method is environmentally friendly and energy-saving, and is suitable for large-scale production. Attached Figure Description
[0036] Figure 1 XRD comparison diagrams of titanium magnesium phosphate materials prepared under different schemes. Detailed Implementation
[0037] The present invention will be further described below with reference to specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.
[0038]
Example
[0039] S2. The mixed slurry after sand milling is dried using a pneumatic spray dryer. The inlet temperature of the spray dryer is 290℃, the outlet temperature is 120℃, and the pressure is 0.4 MPa. After drying, a loose powder is obtained.
[0040] S3. The obtained dry powder is then placed in a high-temperature box furnace for sintering to obtain sintered material. The sintering temperature is 1000℃, the sintering time is 8 h, and the heating rate is 4℃ / min. Afterwards, it is naturally cooled to room temperature, and the sintered material is mechanically dispersed to obtain modified titanium magnesium phosphate material Mg. 0.51 Ti 1.99 Al 0.01 (PO4)3. The XRD diffraction pattern of this material is as follows: Figure 1 As shown, the crystal structure conforms to standard card PDF#82-0297.
[0041] Example 2 x=0.03 S1, magnesium carbonate 8.43 g, titanium pyrophosphate 62.75 g, titanium dioxide 7.08 g, and alumina 0.29 g; these raw materials were added to polyvinyl alcohol and stirred to obtain a slurry with a solid content of 20 wt%, which was then sand-milled. Sand milling conditions: 0.3 mm zirconium beads were used, and the rotation speed was 1800 rpm. Sand milling was completed when the average particle size measured by a laser particle size analyzer was less than 0.3 μm, yielding the mixed slurry.
[0042] S2. The mixed slurry after sand milling is dried using a pneumatic spray dryer. The inlet temperature of the spray dryer is 290℃, the outlet temperature is 120℃, and the pressure is 0.4 MPa. After drying, a loose powder is obtained.
[0043] S3. The obtained dry powder is then placed in a high-temperature box furnace for sintering to obtain sintered material. The sintering temperature is 1000℃, the sintering time is 8 h, and the heating rate is 4℃ / min. Afterwards, it is naturally cooled to room temperature, and the sintered material is mechanically dispersed to obtain modified titanium magnesium phosphate material Mg. 0.53 Ti 1.97 Al 0.03 (PO4)3. The XRD diffraction pattern of this material is as follows: Figure 1 As shown, the crystal structure conforms to standard card PDF#82-0297.
[0044] Example 3 x=0.05 S1, magnesium carbonate 8.43 g, titanium pyrophosphate 60.49 g, titanium dioxide 6.53 g, and alumina 0.46 g; these raw materials were added to polyvinyl alcohol and stirred to obtain a slurry with a solid content of 20 wt%, which was then sand-milled. Sand milling conditions: 0.3 mm zirconium beads were used, and the rotation speed was 1800 rpm. Sand milling was completed when the average particle size measured by a laser particle size analyzer was less than 0.3 μm, yielding the mixed slurry.
[0045] S2. The mixed slurry after sand milling is dried using a pneumatic spray dryer. The inlet temperature of the spray dryer is 290℃, the outlet temperature is 120℃, and the pressure is 0.4 MPa. After drying, a loose powder is obtained.
[0046] S3. The obtained dry powder is then placed in a high-temperature box furnace for sintering to obtain sintered material. The sintering temperature is 1000℃, the sintering time is 8 h, and the heating rate is 4℃ / min. Afterwards, it is naturally cooled to room temperature, and the sintered material is mechanically dispersed to obtain modified titanium magnesium phosphate material Mg. 0.55 Ti 1.95 Al 0.05 (PO4)3. The XRD diffraction pattern of this material is as follows: Figure 1 As shown, the crystal structure conforms to standard card PDF#82-0297.
[0047] Example 4 This embodiment is basically the same as embodiment 3, except that: S3. The obtained dry powder is then placed in a high-temperature box furnace for sintering to obtain sintered material. The sintering temperature is 900℃, the sintering time is 10 h, and the heating rate is 4℃ / min.
[0048] Example 5 This embodiment is basically the same as embodiment 3, except that: S3. The obtained dry powder is then placed in a high-temperature box furnace for sintering to obtain sintered material. The sintering temperature is 1050℃, the sintering time is 6 h, and the heating rate is 4℃ / min.
[0049] Example 6 S1, magnesium carbonate 8.43 g, titanium pyrophosphate 60.49 g, titanium dioxide 6.53 g, chromium oxide 0.69 g; these raw materials were added to polyvinyl alcohol and stirred to obtain a slurry with a solid content of 30 wt%, which was then sand-milled. Sand milling conditions: 0.3 mm zirconium beads were used, and the rotation speed was 1800 rpm. Sand milling was completed when the average particle size measured by a laser particle size analyzer was less than 0.3 μm, yielding the mixed slurry.
[0050] S2. The mixed slurry after sand milling is dried using a pneumatic spray dryer. The inlet temperature of the spray dryer is 290℃, the outlet temperature is 120℃, and the pressure is 0.4 MPa. After drying, a loose powder is obtained.
[0051] S3. The obtained dry powder is then placed in a high-temperature box furnace for sintering to obtain sintered material. The sintering temperature is 1000℃, the sintering time is 8 h, and the heating rate is 4℃ / min. Afterwards, it is naturally cooled to room temperature, and the sintered material is mechanically dispersed to obtain modified titanium magnesium phosphate material Mg.0.55 Ti 1.95 Al 0.05 (PO4)3. The XRD diffraction pattern of this material is as follows: Figure 1 As shown, the crystal structure conforms to standard card PDF#82-0297.
[0052] Comparative Example 1 This comparative example is basically the same as Example 1, except that: S1, magnesium carbonate 8.43 g, phosphorus pentoxide 42.58 g, titanium dioxide 31.92 g; these raw materials were added to polyvinyl alcohol and stirred to obtain a slurry with a solid content of 20 wt%, which was then sand-milled. Sand milling conditions: 0.3 mm zirconium beads were used, and the rotation speed was 1800 rpm. Sand milling was completed when the average particle size measured by a laser particle size analyzer was less than 0.3 μm, yielding the mixed slurry.
[0053] Finally, the titanium magnesium phosphate material Mg was obtained. 0.5 Ti2(PO4)3.
[0054] Comparative Example 2 This comparative example is basically the same as Example 1, except that: S1, magnesium carbonate 8.43 g, titanium pyrophosphate 65.23 g, titanium dioxide 7.68 g; these raw materials were added to polyvinyl alcohol and stirred to obtain a slurry with a solid content of 20 wt%, which was then sand-milled. Sand milling conditions: 0.3 mm zirconium beads were used, and the rotation speed was 1800 rpm. Sand milling was completed when the average particle size measured by a laser particle size analyzer was less than 0.3 μm, yielding the mixed slurry.
[0055] Finally, the titanium magnesium phosphate material Mg was obtained. 0.5 Ti2(PO4)3.
[0056] [Performance Testing] 1. XRD test XRD tests were performed on the modified titanium magnesium phosphate materials or titanium magnesium phosphate materials obtained in Examples 1-6 and Comparative Examples 1-2, and the results are as follows: Figure 1 As shown. Observation Figure 1 It can be seen that the diffraction peaks of the modified titanium magnesium phosphate material prepared in this invention coincide with the diffraction peaks of the titanium magnesium phosphate standard card, indicating that Al 3+ / Cr 3+ Ion-doped magnesium titanium phosphate materials do not change the lattice structure of the main phase of NASICON-type magnesium titanium phosphate.
[0057] Furthermore, comparing Example 1 and Comparative Example 2, it can be found that doping with an appropriate amount of Al... 3+It can effectively suppress the formation of impurity phases (impurity phases appearing around 23° and 27°), thereby reducing the adverse effects of these impurities on ion conduction to a certain extent. This is because in titanium magnesium phosphate, Ti... 4+ By Al 3+ Substitution will introduce more Mg 2+ To maintain electrical neutrality, and to supplement Mg 2+ The impurity phase can be further transformed into magnesium titanium phosphate conductive crystal.
[0058] Examples 1-6 use titanium pyrophosphate and titanium dioxide as the phosphorus and titanium sources of the titanium magnesium phosphate raw material simultaneously; this avoids the problem of material sticking and loss due to the moisture absorption of phosphorus pentoxide, as well as uneven mixing, thereby greatly reducing the presence of impurity phases caused by uneven proportioning or uneven mixing.
[0059] 2. Other performance tests The adhesion of the modified titanium magnesium phosphate material to the crucible was observed in Examples 1-6 and Comparative Examples 1-2 during the preparation process, and the results are recorded in Table 1. The electrical conductivity of the modified titanium magnesium phosphate material obtained in Examples 1-6 and Comparative Examples 1-2 was also tested, and the results are recorded in Table 1.
[0060] The conductivity test method is as follows: The modified titanium magnesium phosphate powder / titanium magnesium phosphate powder prepared in Examples 1-6 and Comparative Examples 1-2 is pressed into tablets under a pressure of 200 MPa using a powder press; after sanding both sides, conductive silver paste is coated on both sides; after drying, electrochemical impedance spectroscopy (EIS) is performed in an electrochemical tester.
[0061] Table 1. Performance Comparison of Titanium Magnesium Phosphate Materials Prepared Under Different Schemes project Chemical formula of the material Does the sintering process result in sticking to the sagger? Conductivity S / cm Example 1 <![CDATA[Mg 0.51 Of 1.99 Al 0.01 (PO4)3]]> no <![CDATA[2.35×10 -4 ]]> Example 2 <![CDATA[Mg 0.53 Of 1.97 Al 0.03 (PO4)3]]> no <![CDATA[3.13×10 -4 ]]> Example 3 <![CDATA[Mg 0.55 Of 1.95 Al 0.05 (PO4)3]]> no <![CDATA[4.01×10 -4 ]]> Example 4 <![CDATA[Mg 0.55 Of 1.95 Al 0.05 (PO4)3]]> no <![CDATA[3.24×10 -4 ]]> Example 5 <![CDATA[Mg 0.55 Of 1.95 Al 0.05 (PO4)3]]> no <![CDATA[3.66×10 -4 ]]> Example 6 <![CDATA[Mg 0.55 Ti 1.95 Cr 0.05 (PO4)3]]> no <![CDATA[3.58×10 -4 ]]> Comparative Example 1 <![CDATA[Mg 0.5 Ti2(PO4)3]]> yes <![CDATA[1.16×10 -4 ]]> Comparative Example 2 <![CDATA[Mg 0.5 Ti2(PO4)3]]> no <![CDATA[1.39×10 -4 ]]> Observing the data on crucible adhesion in Table 1, it can be seen that Examples 1-6 and Comparative Example 1 used titanium pyrophosphate and titanium dioxide simultaneously as the phosphorus and titanium sources for the titanium magnesium phosphate raw material, thus avoiding the problem of commonly used phosphorus sources such as phosphorus pentoxide sticking due to moisture. Therefore, no crucible adhesion phenomenon occurred during the preparation process of Examples 1-6 and Comparative Example 1. However, Comparative Example 1, which used phosphorus pentoxide, showed a significant problem of crucible adhesion.
[0062] Furthermore, observation of the conductivity data shows that, compared to the comparative example of titanium magnesium phosphate material, the modified titanium magnesium phosphate obtained in Examples 1-6 exhibits significantly improved ionic conductivity. This indicates that Al / Cr doping successfully enhanced the conductivity of this NASICON-type titanium magnesium phosphate. The highest room-temperature ionic conductivity, 4.01 × 10⁻⁵, was achieved when the doping concentration was 0.05%. -4 S·cm -1 This is mainly due to Al3+ / Cr 3+ Cationic substituted Ti 4+ This method broadens the migration channels for magnesium ions, introduces more conductive magnesium ions to maintain electroneutrality, increases the number of charge carriers, and improves ionic conductivity. It is important to note that the dopant content should be controlled within a certain range; excessive or insufficient doping is not advisable. This is because excessive doping with exogenous ions may lead to lattice distortion, interfering with the NASICON-type structure suitable for charge carrier migration and causing capacity decay. Insufficient substitution will not achieve the required electrochemical performance and may also generate impurity phases. Therefore, the dopant content should be controlled within a certain range. Furthermore, the test results show that using titanium pyrophosphate as the phosphorus source solves the problem of sticking to the crucible during sintering to a certain extent, improving the convenience of the preparation process.
Claims
1. A modified titanium magnesium phosphate material, characterized in that, The modified titanium magnesium phosphate material is made by adding M... 3+ It is obtained by one-step solid-state sintering of M source, magnesium source, titanium pyrophosphate and titanium dioxide; the general formula is Mg 0.5+x Ti 2-x M x (PO4)3, M is Al or Cr, 0.01≤x<0.06; wherein, magnesium source is in excess; Mg 2+ The impurity phase is further transformed into a conductive crystal of titanium magnesium phosphate; the diffraction peaks of the modified titanium magnesium phosphate material coincide with the diffraction peaks of the titanium magnesium phosphate standard card.
2. The method for preparing a modified titanium magnesium phosphate material as described in claim 1, characterized in that, Includes the following steps: S1, containing M 3+ M source, magnesium source, titanium pyrophosphate, and titanium dioxide are uniformly dispersed in water / alcohol reagent to obtain a mixed slurry; S2. The mixed slurry obtained in S1 is milled, dried, and then sintered to obtain a product with the general formula Mg. 0.5+x Ti 2-x M x (PO4)3 (0.01≤x<0.06) modified titanium magnesium phosphate material; Where M is Al or Cr.
3. The method as described in claim 2, characterized in that, In step S1, the magnesium source is selected from one or more of magnesium carbonate, magnesium oxide, magnesium hydroxide, and magnesium phosphate.
4. The method as described in claim 2, characterized in that, In step S1, the alcohol reagent is selected from any one of ethanol, propylene glycol, and polyvinyl alcohol.
5. The method as described in claim 2 or 4, characterized in that, In step S1, the solid content of the mixed slurry is 15~35 wt%.
6. The method as described in claim 2, characterized in that, In step S2, the average output particle size of the sand mill is less than 0.3 μm, and the rotation speed is 1500-2000 rpm.
7. The method as described in claim 2 or 6, characterized in that, In step S2, the drying method is selected from any one of the following: oven drying, vacuum rake drying, and spray drying.
8. The method as described in claim 2, characterized in that, In step S3, the sintering temperature is 900~1100℃, the sintering time is 6~12 h, and the heating rate is 2~5℃ / min.
9. The application of the modified titanium magnesium phosphate material as described in claim 1 or the modified titanium magnesium phosphate material prepared by the method described in any one of claims 2 to 8 in solid-state batteries.
Citation Information
Patent Citations
Composite positive electrode material and preparation method and application thereof
CN115133009A
Magnesium-series solid electrolyte as well as preparation method and application thereof
CN116565331A
